CAPITAL STRUCTURE, LIQUIDITY, AND STOCK RETURNS - Gharaibeh, Adnan (European Scientific Journal, ESJ, 2014)
This paper investigates how stock returns are influenced by non- profit indicators derived from corporate financial reports, the study used capital structure and liquidity ratio as nonprofit parameters. We examined the financial statements of (15) industrial firms listed on Amman Stock Exchange for the period 2009 to 2012 which intervened by the world financial crisis. The result shows that there is a weak and significant relation between stock returns and liquidity, while the relationship with capital structure was also weak but insignificant. The study concluded that nonprofit indicators were less valued in equity investment decisions during this period which may seem surprising since these indicators represent a bankruptcy risks. Furthermore, this may also be regarded as an evidence of stock market inefficiency which may be verified by examining other profit and nonprofit variables.